Effect of the season and climatic factors on the microbiological quality of raw goat milk in southern Thailand - Binnima, Ni-azanee; Saelim, Thanakorn; Duangrung, Thunyaluk; Wiriyaprom, Ratchakul; Ngasaman, Ruttayaporn; Prachantasena, Sakaoporn (Journal of Advanced Veterinary Research, 2025)
Microbial contamination of raw milk considerably affects the quality and safety of dairy products. Dairy farm environmental factors (e.g., temperature, humidity and milking hygiene) involved with the microbiological quality of raw goat milk were previously elucidated. Until now, the research on the quality of raw goat milk in Thailand is still limited. The current study focused on the variation in microbiological quality (i.e., total bacteria, coliforms, proteolytic bacteria, lipolytic bacteria and thermoduric bacteria) of raw goat milk affected by climatic factors (i.e. rainfall, relative humidity and ambient temperature). Study area included raw goat milk from smallholders in the lower part of Southern Thailand. The results indicated that contamination of total bacteria, lipolytic bacteria, proteolytic bacteria and coliforms was higher during the rainy season than in the dry season (P<0.05), whereas there was no statistical difference (P<0.05) in the thermoduric bacteria in raw goat milk collected during the dry and rainy seasons. The current study revealed a positive correlation between two climatic factors (i.e. rainfall and relative humidity) and four microbiological parameters (i.e. total bacteria, coliforms, proteolytic bacteria and lipolytic bacteria). In addition, the ambient temperature was negatively correlated with the abovementioned four microbiological parameters. No statistical association between thermoduric bacteria and three climatic factors (i.e. rainfall, relative humidity and ambient temperature) was found. To ensure consistently quality of goat milk, farmers should enhance milking hygiene practices during the rainy season, when rainfall and humidity are higher in the dry season.